2014
DOI: 10.2478/s11686-014-0235-1
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the morphology of the juvenile life stages of Paradiplozoon ichthyoxanthon Avenant-Oldewage, 2013 (Monogenea: Diplozoidae)

Abstract: There are eight life stages in the life-cycle of Diplozoon paradoxum and limited knowledge of the life-cycle for other diplozoid genera exists. The aim of this study was to record the number of life-stages of Paradiplozoon ichthyoxanthon obtained from, Labeobarbus aeneus and Labeobarbus kimberlyensis, in the Vaal Dam from 2005 to 2007. Six larval life stages and one adult stage of P. ichtyoxanthon were identified from specimens collected in vitro and in situ. In vitro, eggs hatched after 21 days at 18°C. Eggs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…However, this appeared to change in eggs containing almost fully developed embryos exposed to 120 μg Al/l where the highest percentage of perished, unhatched larvae were present. This is further supported by the observation that embryos in 120 μg Al/l exposure had reached the final stages of development where eye-spots and cilia were clearly visible [ 26 ]. This could be linked to alterations in the permeability of the egg capsule over the developmental period of the oncomiracidia instead of the resistance of embryos decreasing, where it would then be expected that even at low concentrations the unhatched oncomiracidia would have perished before or shortly after hatching.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…However, this appeared to change in eggs containing almost fully developed embryos exposed to 120 μg Al/l where the highest percentage of perished, unhatched larvae were present. This is further supported by the observation that embryos in 120 μg Al/l exposure had reached the final stages of development where eye-spots and cilia were clearly visible [ 26 ]. This could be linked to alterations in the permeability of the egg capsule over the developmental period of the oncomiracidia instead of the resistance of embryos decreasing, where it would then be expected that even at low concentrations the unhatched oncomiracidia would have perished before or shortly after hatching.…”
Section: Discussionmentioning
confidence: 67%
“…The time taken for hatching of eggs of P. ichthyoxanthon to commence was delayed in 120 μg Al/l exposure, while exposure to 30 μg Al/l and 60 μg Al/l appeared to accelerate hatching time of eggs. According to Avenant-Oldewage & Milne [ 26 ] eggs of P. ichthyoxanthon incubated at 18 °C took 21 days for hatching to commence. MacDonald & Jones [ 24 ] found that hatching of eggs of Diplozoon paradoxum occurred 5–6 days after laying at temperatures ranging from 8–27 °C, but indicated that hatching was related to photoperiod and not temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…;Marx and Avenant-Oldewage 1998; Marx 2000a, 2000b;Retief et al 2006;Crafford and Avenant-Oldewage 2009, 2010Watson et al 2012).The UJ group also conducted different studies on aspects of the biology of the interesting Siamese twin monogenean worms of the genus Paradiplozoon(Milne and Avenant- Oldewage 2006;Avenant-Oldewage et al 2012;Milne and Avenant-Oldewage 2012;Avenant-Oldewage and Milne 2014), as well as the description of Paradiplozoon vaalense(Dos Santos et al 2013).…”
mentioning
confidence: 98%